The Adaptive Test of Emotion Knowledge for 3-to 9-Year-Olds: Psychometric Properties and Validity - Voltmer, Katharina; von Salisch, Maria (Frontiers in Psychiatry, 2022)
Children with an advanced knowledge of emotions are generally more socially competent, less likely to suffer from psychopathology, and more likely to succeed in school, both socially and academically. The assessment of children's emotion knowledge has thus gained importance in recent decades - both in psychiatric practice and in developmental and educational psychology. However, there is still a lack of appropriate instruments for assessing children’s emotion knowledge in a performance test reliably, and for a broad age range. The Adaptive Test of Emotion Knowledge (ATEM 3-9) is a newly developed measure which encompasses seven components of emotion knowledge in three to nine-year-olds. The ATEM 3-9 is an adaptive test which uses skip and dropout rules to adjust for children's varying levels of knowledge. In addition to German, the ATEM has been translated into English and Hebrew. The German norming sample of the ATEM 3-9 comprises N = 882 (54% female, 21% bilingual) children between the ages of three and nine years, who were divided into seven age groups. Test items, which are ordered according to the item response theory, showed a good fit to a seven-dimensional model reflecting the seven components. The internal consistencies of the dimensions are acceptable to good. Construct validity was examined by means of correlations with other measures of emotion knowledge, as well as measures on language skills and executive functions in a subsample. This resulted in medium size correlations in the expected directions. In addition, children with externalizing and internalizing disorders who were recruited in psychiatric in- and outpatient clinics showed deficits in various components of emotion knowledge when compared to their agemates in the norming sample. Overall, the ATEM 3-9 is well suited to measure individual components of emotion knowledge in children and to obtain a differentiated picture of the various aspects of emotion knowledge. The ATEM 3-9 thus supports the investigation of the development of social-emotional competencies in normative development (e.g., school readiness) and in social-emotional-learning interventions. Furthermore, it is suitable as an instrument for the differentiated assessment of (progress of) children's emotion knowledge in clinical child psychology and psychiatry.